Assessing the effectiveness of zoster vaccine live: A retrospective cohort study using primary care data in the United Kingdom. Issue 46 (12th November 2018) - Matthews, Ian; Lu, Xiaoyan; Dawson, Hazel; Bricout, Hélène; O'Hanlon, Helen; Yu, Eric; Nozad, Bayad
Abstract: Background: Herpes zoster (shingles) is a common viral disease increasing in risk and severity with age. Post-herpetic neuralgia (PHN), a complication of shingles, causes severe pain impacting quality of life (QoL). Zoster Vaccine Live (ZVL), a licensed vaccine for the prevention of shingles in the United Kingdom (UK), is part of the national immunisation programme (NIP) for adults aged 70–79. Public Health England (PHE) reports show shingles vaccine coverage varies, but is typically 50–60% across eligible cohorts. Materials/methods: This retrospective, matched cohort study was conducted using The Health Improvement Network (THIN) UK primary care database. Individuals aged 70–79 were classified based on their vaccination status between September 2013 and May 2016. Risk and incidence rates for shingles were calculated for both groups over the duration of the study (mean 1.2 years). Vaccine effectiveness (VE) was calculated using the equation 1-relative risk (RR) for shingles and PHN. Results: Within the total cohort (n = 295, 135), 70, 867 (24%) were vaccinated and 224, 268 (76%) were unvaccinated. 2435 (0.83%) patients developed shingles: 241 (0.34%) among the vaccinated and 2194 (0.98%) among the unvaccinated. The VE for preventing shingles was 65.3% (95% CI: 60.3–69.6%). The incidence rate in the vaccinated group was 2.95 (95% CI: 2.59–3.34) vs 8.02 (95% CI: 7.68–8.36) per 1000 person years in the unvaccinated group. Risk of PHN was 0.02% and 0.06% in the respective vaccinated and unvaccinated groups. The VE for preventing PHN was 72% (95% CI: 50.0–83.9%). PHN incidence rates were 0.16 (95% CI: 0.08–0.27) and 0.53 (95% CI: 0.44–0.62) per 1000 person years in the vaccinated and unvaccinated groups, respectively. Conclusions: ZVL reduced the risk of shingles among an elderly population. Given the negative impact of shingles and PHN on QoL, the benefits of vaccination are clear. Improving uptake in the UK is needed in this population.